EVALUATION OF NEWER INSECTICIDES FOR THE MANAGEMENT OF MYZUS PERSICAE (SULZER) - naga, kailash chandra (Potato Journal, 2022)
Green peach aphid, Myzus persicae (Sulzer) (Aphididae: Hemiptera) is one of important pest which causesdirect and indirect losses to many horticultural crops. To deal with this pest insecticide application remains the principalmethod to avoid its losses. Therefore, the present study was aimed to evaluate two insecticides with novel mode of actionas an alternative to the existing insecticides used for management of M. persicae. Further leaf dip method was followedto evaluate the test chemicals against M. persicae. Probit analysis and LC50 data suggest that flonicamid is as effective asimidacloprid. The flonicamid also has different mode of action and can be used as an alternate chemical to manage M.persicae in potato and other crop ecosystems. This is the first study that indicates insecticidal resistance in M. persicaepopulation in India.